PEMBERDAYAAN IBU HAMIL DENGAN PEMBERIAN EDUKASI PIJAT OKSITOSIN UNTUK MEMPERLANCAR ASI PADA MASA MENYUSUI DI DESA GAYAMAN MOJOANYAR MOJOKERTO - Nurun Ayati Khasanah; Ferilia Adiesti; Citra Adityarini Safitri (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2023)
Because breast milk is crucial to a baby's development, mothers should grasp the need of exclusively nursing their newborns. Giving an oxytocin the non-pharmacological techniques that can be used to encourage mothers' milk production. Exclusive breastfeeding is also greatly influenced by moms' knowledge levels. The study's methodology included socializing, questionnaire completion, education, and post- and pre-testing after the education phase. This community service project's objective is to inform people about oxytocin massage, which facilitates breastfeeding. The study's findings, which were based on responses from 20 pregnant women, showed that 13 respondents (38.24%) had sufficient knowledge about oxytocin massage in pregnant women.